(untitled) (Al-Academy, 2026)
Pictorial space is the starting point and starting point for constructing any artwork. It is the foundation and basis upon which the elements of composition are built. Its artistic and philosophical connotations and display techniques have varied with the development of the artistic movement over time. Therefore, the current research aims to answer the following question: How does pictorial space appear in the drawings of art teachers, and what are the techniques for displaying it? The research aimed to: reveal how pictorial space is formed, and the techniques for displaying it in the drawings of art education teachers. To achieve this goal, the researcher adopted the descriptive and analytical approach. The research community consisted of (35) artistic paintings, all of which represented the research sample. The researcher then designed a form to analyze the artistic outputs (drawings), which was applied after a narrative analysis of the works. To arrive at the results, the researcher extracted the weighted mean and percentage weight for the sub-items in the analysis form. The results were consistent with the results of the confidential analysis, which confirms their validity. Among the most important results of the research: Teachers prefer perspective space and flat space in their work, and they used linear and color perspective techniques to a large extent in shaping the space of the painting, while they used collage techniques, gradation in size and texture, and rhythm techniques to a small extent